Cattle Bile Arisaema Aqueous Extracts Protect Against Febrile Seizures in Rats Through Regulating Neurotransmitters and Suppressing Neuroinflammation - Su, Fa-Zhi; Bai, Chen-Xi; Luo, Yumeng; Zhang, Wen-Sen; Cui, Na; Wang, Yang-Yang; Sun, Yan-Ping; Zhu, Wen-Bo; Zhao, Ming-Yang; Yang, Bing-You; Kuang, Hai-Xue; Wang, Qiu-Hong (Frontiers in Pharmacology, 2022)
Cattle bile Arisaema (CBA) is a traditional medicine in the treatment of febrile seizures (FS) for thousands of years in China. But its application is greatly limited due to cost reasons, pig bile Arisaema (PBA) is the main commercial product instead. Additionally, the underlying mechanism of CBA for the treatment of FS still remains unknown. In this study, we investigated the anti-convulsant effect and potential mechanism of CBA aqueous extract at the first time through a hot water bath induced FS rat model. Our results showed that pre-treatment with CBA dramatically lowered the incidence rate and generation times, and prolonged the latency of FS. In addition, CBA effectively ameliorated neuronal damage and regulated neurotransmitter disorder induced by FS in the rat hippocampus. The enzyme-linked immunosorbent assay, western blotting, immunohistochemical and qRT-PCR results exhibited that CBA suppressed the expression of GFAP, TLR4, NF-κB, HMGB1, NLRP3, TNF-α, IL-1β and IL-6, and consequently inhibited the neuroinflammation induced by FS. Interestingly, although CBA and PBA aqueous extracts possessed the same trend on the changes caused by FS, the improvement of FS by CBA is markedly better than PBA. These findings indicate that CBA exerts protective effect on febrile seizures through regulating neurotransmitter disorder and suppressing neuroinflammation.